Utilization of Ceiba Pentandra seed oil as potential feedstock for biodiesel production - Yusup, S. (Nova Science Publishers, Inc., 2013)
The utilization of Ceiba Pentandra seed oil as potential feedstock for biodiesel production has been explored. About 28 wt/wt of Ceiba Pentandra seed oil was obtained from the extraction process. Ceiba Pentandra seed oil which contains high free fatty acid (FFA) was pre-treated using acid-catalyzed esterification process. Transesterification process had been carried out using L9 Taguchi method. It was found that, the highest yield of Ceiba Pentandra biodiesel which is 90.52 was obtained at reaction temperature of 70oC and methanol-to-oil molar ratio of 10:1. The biodiesel property of Ceiba Pentandra seed oil Methyl Ester has been characterized and it meets the properties of biodiesel as stated in standard method of ASTM D6751 and EN14214. Â© 2013 by Nova Science Publishers, Inc. All rights reserved.